Concurrent myeloid sarcoma, atypical teratoid/rhabdoid tumor, and hypereosinophilia in an infant with a germline SMARCB1 mutation. Issue 9 (23rd January 2017) - Metts, Jonathan L.; Park, Sunita I.; Soares, Bruno P.; Fong, Cindy; Biegel, Jaclyn A.; Goldsmith, Kelly C.
Abstract: We report a 1‐year‐old female child presenting with hypereosinophilia who was found to have concurrent myeloid sarcoma and a central nervous system (CNS) atypical teratoid/rhabdoid tumor (AT/RT). She was later found to have a germline mutation in SMARCB1. Concurrent hematologic malignancy and CNS AT/RT have not previously been described in the context of a SMARCB1 loss‐of‐function germline mutation.